Predictive medicine between rigors of technology and what it should be of morality - Boudjlal, Nadia (Journal of Human Sciences, 2022)
Thanks to significant advances in genetics we are not only getting bather at diagnosing disease, but also at predicting disease. Predictive medicine is an exciting new approach to healthcare, that analytical technique to make predictions about the future health of patient. This ideal and the technologies developed to realize it have been the subject of much ethical concerns about predictive medicine and point out her here this have coevolved with scientific and technological developments in the field, and to what should be considered of predictive testing and who should define this, the responsibility for one’s healthy and the predictive testing on society.